Analisis Motivasi Kerja dan Lingkungan Kerja serta Pengaruhnya terhadap Kinerja Karyawan di Hotel Kridawisata Lampung - Revirani, Selvie; Nia Lefiani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study aims to analyze the influence of intrinsic motivation, work atmosphere, and work environment on employee productivity and performance at Hotel Kridawisata Bandar Lampung. A total of 30 employees from the hotel were selected as the population for this study, using a saturated sampling approach to obtain a representative sample. Data was collected through questionnaires and analyzed using SPSS version 25.0 to examine the correlation and influence between independent variables (work motivation and work atmosphere) and employee performance. The analysis revealed a significant positive correlation between employee work motivation and their performance, with a regression coefficient of 0.389. This indicates that higher work motivation leads to better performance. Additionally, the work atmosphere had a positive and significant impact on employee performance, with a regression coefficient of 0.467. These findings suggest that a supportive and comfortable work atmosphere can significantly enhance employee performance. Based on the obtained R-square value of 0.493 or 49.3%, it can be concluded that work motivation and work atmosphere have an influence on employee performance at Hotel Kridawisata. In other words, approximately 49.3% of the variation in employee performance can be explained by these two factors, while the remaining 50.7% is influenced by other factors not covered in this study. This highlights the importance of both work motivation and the work environment in driving employee performance. Therefore, it is recommended that the management of Hotel Kridawisata continue to improve employee motivation and create a more conducive work atmosphere. This will not only enhance employee performance but also contribute to improving the quality of hotel services, which in turn can increase guest satisfaction and the hotel's operational success.